Long‐term effect of medical treatment of diarrhoea in 377 patients with SeHCAT scan diagnosed bile acid malabsorption from 2003 to 2016; a retrospective study. Issue 7 (24th January 2018) - Damsgaard, B.; Dalby, H. R.; Krogh, K.; Jørgensen, S. M. D.; Arveschough, A. K.; Agnholt, J.; Dahlerup, J. F.; Jørgensen, S. P.
Summary: Background: Excessive amounts of bile acids entering the colon due to bile acid malabsorption cause chronic bile acid diarrhoea. Diagnosis is possible by measuring the retention fraction of orally ingested 75 Selenium homotaurocholic acid (SeHCAT). The knowledge of long‐term effects of medical treatment is sparse. Aim: To describe diarrhoea, adherence to treatment, treatment effects and quality of life in a large, well‐defined cohort of patients with bile acid diarrhoea. Methods: A retrospective survey was performed among 594 patients with bile acid malabsorption verified by SeHCAT scans at our unit between 2003 and 2016. Questionnaires about medical history, diarrhoea, use of medication, and quality of life scores were mailed to all patients. Results: Among 594 patients 377 (69%) responded. Among respondents, 121 (32%) had bile acid diarrhoea due to ileal disease or resection (type 1), 198 (52%) idiopathic bile acid diarrhoea (type 2) and 58 (16%) bile acid diarrhoea due to other non‐ileal disease, mainly cholecystectomy (type 3). At follow‐up, half of the patients, 184 (50%), reported improvement of diarrhoea. However, 273 patients (74%) still reported diarrhoea and 234 (62%) regularly used anti‐diarrhoeal medication. In spite of treatment, 235 (64%) considered reduced quality of life by diarrhoea and 184 (50%) reported that diarrhoea was unaltered or worse than before established diagnosis. Conclusion: Many patients with bile acid diarrhoea continue to have bothersome diarrhoea in spite of correct diagnosis and treatment.